Theoretical and Methodological Foundations for the Formation of Communicative Competence of Medical Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Currently, there is a rapid and intensive development of medical science. In accordance with this, new goals and objectives are put forward in the preparation of medical specialists, which are reflected in the federal state standards of higher professional medical education. These goals and objectives concern not only profile and special medical disciplines, but also disciplines of the basic general education cycle. This article will focus on teaching English at undergraduate and postgraduate levels of education.